Intelligent 3D Vision System for Robotic System integration - Diogo Pina Brandão (2019)
This project has as main objective the development of a vision system capable of detecting rectangular boxes, such as a medicine package. The information obtained from the developed vision algorithm serves as input for a robotic arm to move the boxes to the desired locations.